Akar Wangi (Vetiveria zizanioides, Linn Nash) Sebagai Tanaman Konservasi Tanah Pada Usahatani Lahan Kering - Jaka Suyana (PRIMA: Journal of Community Empowering and Services, 2025)
Upland farming systems are usually located in the middle and upstreams of the Watershed as well as has many problems, ie: marginal land conditions, prone to erosion, limited water availability, limited cultivation technology, and low farm income. Vegetative of conservation technology method much recommended in action of Soil and Water Conservation (SWC) on upland because besides suppress erosion, also can ensure increasing land productivity and easy applied by farmers. Vetiver plant besides can growth in all fields and climate, also has many functions. On the island of Java, vetiver planted by many farmers in the region Garut Regency West Java Province which is known as vetiver of Garut variety and in Gunung Kidul Regency Daerah Istimewa Yogyakarta Province which is known as vetiver of Wonosari variety. Vetiver plant can be used for soil conservation and slope stabilization. Vetiver plant can be used for support various technologies of SWC that already exists. Vetiver can be used as hedges, can be planted as strips of strengthened terrace and planted as row of plants according to the contour. Vetiver plant after certain age can be trimmed periodically to be utilized as a mulch for plant residues. Farmer on upland can use vetiver as a conservation plant and land rehabilitation independently to create a farming system which is eco-friendly.